2002
DOI: 10.1128/jvi.76.14.6957-6965.2002
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Receptor Recognition by a Minor-Group Human Rhinovirus (HRV): HRV Serotype 1A Distinguishes between the Murine and the Human Low-Density Lipoprotein Receptor

Abstract: Human rhinoviruses (HRV) of the minor receptor group use several members of the low-density lipoprotein receptor superfamily for cell entry. These proteins are evolutionarily highly conserved throughout species and are almost ubiquitously expressed. Their common building blocks, cysteine-rich ligand binding repeats about 40 amino acids in length, exhibit considerable sequence similarity. Various numbers of these repeats are present in the different receptors. We here demonstrate that HRV type 1A (HRV1A) replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Human colorectal adenocarcinoma (CaCo-2), human lung carcinoma (A549), human larynx epidermoid carcinoma (Hep-2C), mouse embryo fibroblast (3T3), hamster kidney (BHK21), rabbit kidney (RK13), canine kidney (MDCK) and bovine kidney (MDBK) cell lines were purchased from ATCC. Human neuroblastoma (SK-N-SH) cells were kindly provided by Antti Vaheri (University of Helsinki, Finland ) cells (Reithmayer et al, 2002) and intracellular adhesion molecule (ICAM-1)-expressing M4 cells were kindly provided by Dieter Blaas (Medical University of Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Human colorectal adenocarcinoma (CaCo-2), human lung carcinoma (A549), human larynx epidermoid carcinoma (Hep-2C), mouse embryo fibroblast (3T3), hamster kidney (BHK21), rabbit kidney (RK13), canine kidney (MDCK) and bovine kidney (MDBK) cell lines were purchased from ATCC. Human neuroblastoma (SK-N-SH) cells were kindly provided by Antti Vaheri (University of Helsinki, Finland ) cells (Reithmayer et al, 2002) and intracellular adhesion molecule (ICAM-1)-expressing M4 cells were kindly provided by Dieter Blaas (Medical University of Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…How-ever, it was subsequently shown that RV16 replicates in mouse cells after transfection of viral RNA (10). Additional studies have shown replication of RV1A in cultured mouse fibroblasts (11) and replication of RV1B in LA-4 mouse airway epithelial cells (12). We have also observed replication of RV1B in primary mouse tracheal epithelial cells as evidenced by detection of cytopathic effect, cytokine induction, and viral 3C protease expression with intact but not ultraviolet (UV)-inactivated virus (P. Jourdan, J. Burnet, and S. Johnston, unpublished data).…”
mentioning
confidence: 97%
“…Members of the LDLR are highly conserved throughout evolution and are ubiquitously expressed. Therefore, apart from differences in affinity, minor-group HRVs bind to cells of many species, but most of them, in particular HRV2, do not replicate (27). Therefore, a human cell line had to be used in surrogate receptor studies; however, this either required the prevention of endocytosis via the natural receptors or neutralization of the virus by suitable antibodies.…”
mentioning
confidence: 99%